2002
DOI: 10.1590/s0102-86502002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Octreotida no tratamento de fístulas entéricas de ratos

Abstract: Somatostatina e seu análogo sintético octreotida são as drogas mais amplamente utilizadas para tratar fístulas enterocutâneas. Todavia, as evidências suportando seu uso ainda são insuficientes. Objetivo: Investigar os efeitos terapêuticos de octreotida em um modelo experimental de fístula enterocutânea. Métodos: Em trinta ratos machos Wistar com peso 210± 17g foi confeccionada cirurgicamente uma fístula jejunocutânea. Os animais foram aleatoriamente divididos em três grupos de dez. No grupo A, administrou-se u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…In previous experimental work in dogs, the fistulas were clinically sealed using the same method; at the end of the experiment we showed that the all the fistulas were histologically closed and no damage was observed in the bowel [4]. In our hospital, patients whose ECFs resulted in electrolyte imbalances, malnutrition, sepsis and other factors influencing the outcome of their fistulas were treated with parenteral/enteral nutrition and octreotide [17]. In addition, all the priorities in management recommended by Dudrick et al [5] were considered and implemented.…”
Section: Discussionmentioning
confidence: 98%
“…In previous experimental work in dogs, the fistulas were clinically sealed using the same method; at the end of the experiment we showed that the all the fistulas were histologically closed and no damage was observed in the bowel [4]. In our hospital, patients whose ECFs resulted in electrolyte imbalances, malnutrition, sepsis and other factors influencing the outcome of their fistulas were treated with parenteral/enteral nutrition and octreotide [17]. In addition, all the priorities in management recommended by Dudrick et al [5] were considered and implemented.…”
Section: Discussionmentioning
confidence: 98%
“…Outra condição clínica, também responsável por altas taxas de morbimortalidade e grande volume de hospitalizações de emergência, é o sangramento digestivo alto 19 . Não são infreqüentes complicações pós-operatórias como fístulas gástricas com ou sem sangramento, ou situações em que o paciente está fazendo uso de octreotide e acaba por necessitar de algum procedimento cirúrgico gástrico (sangramento ou ressangramento, neoplasias, carcinomatoses) 2,8,14 .…”
Section: Abcddv/553unclassified
“…Male rats were chosen for the experiments to prevent eventual hormonal bias and to standardize the groups. We reviewed the literature and found an article in which the fistula model was performed and maintained with a Kehr drain [33], which would not be an ideal model for our experiment because it would be better if the fistula were totally closed. Thus, we decided to perform the procedure as described in the Methods section.…”
Section: Introductionmentioning
confidence: 99%